2008
DOI: 10.1097/hjh.0b013e328312c889
|View full text |Cite
|
Sign up to set email alerts
|

Basic fibroblast growth factor inhibits ventricular remodeling in Dahl salt-sensitive hypertensive rats

Abstract: bFGF can inhibit the progression of ventricular remodeling by inhibiting interstitial fibrosis and promoting angiogenesis without decreasing blood pressure in hypertensive heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Our findings are consistent with the work of others who observed that FGF-2 regulates TGFβ1-mediated myofibroblast activity in non-cardiac derived cells [ 26 - 29 ]. Furthermore, and in support of our findings, Suzuki and co-workers documented an anti-fibrotic effect with addition of exogenous FGF-2 to the hearts of hypertensive rats [ 30 ]. To explain a possible mechanism of action, Cushing and co-workers showed that FGF-2 stimulates MAPK signaling and blocks the localization of SMADs into the nucleus.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings are consistent with the work of others who observed that FGF-2 regulates TGFβ1-mediated myofibroblast activity in non-cardiac derived cells [ 26 - 29 ]. Furthermore, and in support of our findings, Suzuki and co-workers documented an anti-fibrotic effect with addition of exogenous FGF-2 to the hearts of hypertensive rats [ 30 ]. To explain a possible mechanism of action, Cushing and co-workers showed that FGF-2 stimulates MAPK signaling and blocks the localization of SMADs into the nucleus.…”
Section: Discussionsupporting
confidence: 88%
“…But after tanshinone IIA treated, TGF-β1 secretion was decreased and bFGF secretion was increased significantly than 5%GS group. bFGF is capable of suppressing TGF-β1-induced fibroblast differentiation [53] and limiting progressive fibrosis [54]. TGF-β1, after binding to its receptors, activated downstream mediators that leaded to classic Smads signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, others studies point to an anti-fibrotic effect of FGF-2. In Dahl salt-sensitive rats FGF-2 inhibited interstitial fibrosis and then the progression of ventricular remodeling [169] . Moreover, it was observed that lo-FGF-2 was able to attenuating ECM remodeling by myofibroblasts cultured within a 3D collagen matrix [170] .…”
Section: Fibrosismentioning
confidence: 96%